Arms, Influence and the Treaty on the Prohibition of Nuclear Weapons. Issue 3 (4th May 2019) - Egeland, Kjølv
Abstract : The TPNW challenges the legitimacy of nuclear deterrence, but it would not eliminate deterrence in practice.